ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНИҢ НОМИНАЦИЯСЫНДА НЕГАТИВЛИК ПРИНЦИПИ - Қурбанов, М.Д. (FAN va JAMIYAT, 2022)
The article analyzes the process of naming toponyms, including oikonyms, which take into account the human factor and the principles of naming. In particular, the principle of negativity in the nomination of oikonyms, the transformation of small details into the main character - a motive, is explained using the example of local toponyms. On this occasion, the opinions of Russian and Uzbek scientists are also cited. The article also explains the importance of the research subject for the Karakalpak toponymy.